Flood and fury: Old Testament violence and the Shalom of God - Lynch, Matthew J. (InterVarsity Press, 2023)
Old Testament violence proves one of the most troubling topics in the Bible. Without softening or ignoring the most troubling realities of the text, Old Testament scholar Matthew Lynch addresses violence related to misogyny, racism, and nationalism in the Old Testament, yielding surprising insights into the goodness and mercy of God.